Effect of Commitment, Compensation, and Leadership on Employee Performance and Sharia Engagement as Variable Intervening - Indira Basalamah; H. Mansyur Ramli; H. Bahar Sinring; Roslina Alam (AIBPM Publisher, 2019)
Sharia engagement is an individual, physical, emotional and spiritual attachment that is influenced by belief, justice, balance, fredoom and respontibility towards the organization. The object of research is the employees of sharia banking located in Makassar City. Through cluster tehniques sampling of samples processed in the study were 185 emplyees spread across 13 sharia banking offices. Using structural equation modeling (SEM) the results of the study show that organizational commitment, compensation, and leadership directly have a significant positive effect on sharia engagement. Whereas, indirectly organizational commitment, compensation, and leadership have a positive and insignificant effect on employee performance. Then, through Syariah Engagement organizational commitment, compensation, and leadership have a significant positive effect on the performance of Islamic Banking employees in Makassar City. Keywords: Commitment, Compensation, Leadership, Sharia Engagament, and Employee Performance